Bending of an infinite elastic plate with Dirichlet boundary conditions. (28th April 2020) - Constanda, Christian; Doty, Dale
Abstract : A generalized Fourier series method is constructed for the numerical approximation of the solution of the Dirichlet boundary value problem in the theory of bending of an infinite elastic plate with a hole. The qualitative analysis is exemplified be means of two numerical cases and associated graphical illustrations that support the accuracy and efficiency of the procedure.